PENGEMBANGAN SISTEM INFORMASI MANAJEMEN BK BERBASIS DIGITAL UNTUK MENINGKATKAN EFEKTIVITAS LAYANAN - Redita Amalia Fasa; Athallah Nadhif Baktiadi; Rima Faradillah Wati Firdaus Wiyono; Muhamad Hanifudin; Imanda Riski Tri Buana (Cahaya Ilmu Bangsa Institute, 2025)
Guidance and Counseling services, which are often hindered by limited resources and manual data management, can be optimized through the application of information technology. An information system is designed to facilitate the collection, management, and analysis of data related to Guidance and Counseling services, as well as to provide ease of interaction for students and counselors. The development of this system involves designing software with efficient data integration and the provision of in-depth reporting. By analyzing aspects of Guidance and Counseling administration, additional activities conducted by Guidance and Counseling teachers, and professional development, it is essential to enhance the quality of Guidance and Counseling services.